2021
DOI: 10.1111/exd.14409
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor at the forefront of host‐microbe interactions in the skin: A perspective on current knowledge gaps and directions for future research and therapeutic applications

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
(115 reference statements)
0
10
0
Order By: Relevance
“…12 Interestingly, the skin microbiome produces tryptophane metabolites that can also activate AhR, and may contribute to homeostasis of normal skin. 13,14 Tapinarof can activate the nuclear factor erythroid 2-related factor antioxidant signalling pathway, and has anti-bacterial properties. 15,16 Notably, AhR modulation to treat skin diseases has been used for more than a century, as tar, previously a common treatment for psoriasis, has been shown to be an AhR agonist.…”
Section: Ech a N Ism Of Ac Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Interestingly, the skin microbiome produces tryptophane metabolites that can also activate AhR, and may contribute to homeostasis of normal skin. 13,14 Tapinarof can activate the nuclear factor erythroid 2-related factor antioxidant signalling pathway, and has anti-bacterial properties. 15,16 Notably, AhR modulation to treat skin diseases has been used for more than a century, as tar, previously a common treatment for psoriasis, has been shown to be an AhR agonist.…”
Section: Ech a N Ism Of Ac Tionmentioning
confidence: 99%
“…The mechanism of AhR‐mediated cellular regulation is complex and still being elucidated; AhR effect on gene expression depends on the ligand to which it binds 12 . Interestingly, the skin microbiome produces tryptophane metabolites that can also activate AhR, and may contribute to homeostasis of normal skin 13,14 . Tapinarof can activate the nuclear factor erythroid 2‐related factor antioxidant signalling pathway, and has anti‐bacterial properties 15,16 .…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The AhR can be activated by metabolites of bacteria such as Pseudomonas aeruginosa [10] or members of the skin microbiota, such as Malassezia yeasts [16]. Although the role of the AhR in cutaneous defense is still emerging there is growing evidence that it plays an important role in skin-microbe interaction [14]. Several reports have shown that the AhR is crucial for the maintenance of skin barrier function [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The AhR is a ligand-activated transcription factor involved in xenobiotic metabolism, epidermal barrier formation, immune signaling, and immune cell differentiation [10][11][12]. AhR is activated upon binding of various low-molecularweight ligands; the receptor is expressed in various tissues, particularly high expression is found in the liver and in barrier organs such as gut and skin [13,14]. There is increasing evidence that the AhR plays a major role in host defense [11,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Short-lived AHR ligands include UV-induced endogenous tryptophan metabolites [11] (hence the postulated role for AHR-mediated therapeutic effects of UV therapy in PSo). Other metabolites can be formed by members of the skin's microbiome, and dietary plant constituents, as well as several pharmaceutics [12][13][14][15]. Upon activation, AHR signaling is known to regulate a plethora of cellular processes, e.g., embryonic development [16], keratinocyte proliferation and differentiation [17], epidermal barrier formation [14,18], immune cell development [19], angiogenesis [20], and many more [16,18,19,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%